Primary ovarian CIC-rearranged sarcoma in a child: a rare case report and review of the literature - Ke, Liqin; Liu, Lili; Wu, Ying; Sun, Yun; Wang, Yongjiao; Xia, Jiahui; Zhang, Wen (Frontiers in Medicine, 2025)
IntroductionCIC-rearranged sarcoma (CRS) is a rare type of high-grade undifferentiated small round cell sarcoma characterized by a range of possible CIC gene rearrangements. It develops predominantly in the deep soft tissues of the limbs and trunk in young individuals (total range, 0.5–83 years; mean, 27–37 years; median, 24.5–33 years), and less commonly in bone and viscera. The occurrence of this sarcoma in the female reproductive tract is very rare, and it has not yet been described in the ovary.Case presentationWe report a CRS case that arose from the left ovary in a 5-year-old girl. Histologically, the tumor was lobulated or leaf-shaped, with a fibrotic septum composed of closely arranged small- to medium-sized round cells and short spindle-shaped cells. In addition, the neoplastic cells exhibited multifocal membrane positivity for CD99 and diffuse positivity for WT1, TLE1, FLI‑1, P53, INI-1, and Calretinin, CD56 focal positive, while it was negative for ETV4. Fluorescent in situ hybridization analysis showed CIC-positive split signals.ConclusionCRSs are highly aggressive tumors. Rare CRSs have been reported in the female genital tract, and they are often difficult to diagnose. Especially in cases with atypical morphology and immunohistochemistry, it is necessary to integrate molecular features in the diagnosis of undifferentiated neoplasms.